Kontradiksi Aturan Pemulasaraan Jenazah di Indonesia - Nabil; Bambang Sukoco (Perspektif Hukum, 2022)
The Regulation of the Indonesian Medical Council on Educational Standards for Forensic and Medicolegal Specialists states that the burial of corpses includes level 3 competence, namely carrying out supervision. Meanwhile, in the Government Regulation concerning the Implementation of the Hospital Sector, it is stated that for the relocation of corpses services are given to non-health workers. Based on this, the author wishes to examine the legal basis, authority, and responsibility for the negligence of the funeral service. This study used a method in the field of law in a juridical normative with statute approach. This study aims to determine the rules relating to funeral services that are not in accordance with the principles and hierarchy of laws and regulations and cause confusion for forensic and medicolegal specialists in practicing and for law enforcement will cause a problem regarding the complexity of assessing the element of error in negligence. funeral practices.